Analisis Penerapan Blue Ocean Strategy pada Kedai Kopi di Kabupaten Pringsewu di Era Pandemi COVID-19 - Wahyudi Wahyudi Wahyudi; Ayi Ahadiat Ahadiat (Syntax Idea, 2022)
The rapid development of the world creates increasingly fierce competition in the business world. This is also exacerbated by the emergence of the COVID-19 pandemic which has spread to various countries. The presence of the COVID-19 pandemic has affected many companies, both large and small. However, one sector that is still capable of molars is Micro, Small and Medium Enterprises (MSMEs). The purpose of this study is to explain and describe the differences in the implementation of business strategies at coffee shops in Pringsewu Regency during 2021 which is the COVID-19 pandemic period and help formulate strategy improvements using the eliminate-reduce-increase-create strategy canvas and blue ocean strategy index. . This study uses descriptive qualitative research by selecting the object of research are three MSME Coffee Shops in Pringsewu Regency. Sources of data used include primary and secondary using interview techniques to three coffee shops and documentation. The analytical methods used in this research are data reduction, strategy canvas, eliminate – reduce – increase – create and order strategies or blue ocean strategy indexes. Based on the results of research conducted, the COVID-19 pandemic has greatly affected MSMEs in Coffee Shops in Pringsewu Regency. The outbreak of COVID-19 has disrupted the operations of the Coffee Shop MSMEs that are currently being run. Government policies taken to suppress the spread of the COVID-19 pandemic have also reduced coffee shop visitors drastically. Regarding the implementation of business strategies, this study found that in general MSME coffee shops in Pringsewu Regency have not implemented the Blue Ocean Strategy, but are still struggling with the Red Ocean Strategy.